The Use of Google Sites-based Electronic Modules in Science Learning Against Digital Literacy of Junior High School Students - Imesta Zulfanida Ernest; Mulya Dwi Putra M (Jurnal Pendidikan Indonesia, 2023)
Learning in the 21st century requires innovation by utilizing technology as a learning resource for students. Integrating technology into learning has an important role to improve students' skills. One of the integrations of technology is the use of Google Sites-based Electronic Modules which are used as learning resources in science learning. This study aimed to analyze the digital literacy of junior high school students using Google Sites-based electronic modules. The population of this study included class VII students using the cluster random sampling technique. This research includes quasi-experimental research. The design used is the post-test-only control group design using angles. This study uses an instrument in the form of a questionnaire. Analyzing data is using the independent sample t-test. Based on the results of the questionnaire analysis, it is known that the digital literacy of students in the experimental class is superior with an average proportion of 48%. The results of the analysis of the independent sample t-test were Sig (2-tailed) 0.000, which means that there are differences in the digital literacy of junior high school students using electronic modules based on Google sites in science learning. It can be concluded that electronic modules based on Google sites can improve digital literacy. Electronic module based google sites can also bring up students' digital literacy skills.